ANALISIS KUALITAS LINGKUNGAN HIDUP DI INDONESIA - Rahma Andini Eriyanto (2023)
The environment plays an important role in maintaining the balance of the ecosystem and ensuring the availability of natural resources. Damage to the environment is often seen as a "cost" that must be paid for the "benefits" of economic development. Exploitation to use resources that are not careful can increase vulnerability, this is a consequence of problems that cannot be avoided.. For this reason, sustainable development is needed through the pillars of the Sustainable Development Goals (SDGs) approach which includes environmental issues, namely goals 6, 12, 13, 14 and 15. This research aims to conduct an assessment related to environmental quality in 34 provinces in Indonesia. The method used is Multi Criteria Decision Making through sustainability analysis using PROMETHEE software with the observation years 2020 and 2022. The results of the study showed that the assessment of environmental quality was reviewed based on natural, social and economic dimensions which were represented by 11 criteria that had positive and negative contributions to environmental quality. North Kalimantan Province is at the top with a Phi value of 0.4215 and Banten Province is at the bottom with a Phi value of -0.6033. In 2022 there will be a shift in order that West Papua Province is at the top with a Phi value of 0.5895 from the previous position in second place in 2020 and DKI Jakarta Province has experienced a decline in environmental quality with the lowest Phi value of -0.5813.